REHABILITATION OF ICE-HOCKEY PLAYERS AFTER SPORT-RELATED CONCUSSION - Sekretnyi, V. A.; Nekhanevych, O. B. (Rehabilitation and Recreation, 2022)
The aim of study is to develop the criteria for early rehabilitation after sport-related concussions (SRC) with ice-hockey players. 60 professional ice-hockey players age from 17 to 30 years old (average age 22.7±0.8) were included in study. Methods of study: somatoscopy and somatometry, assessment of autonomic nervous system (ANS), assessment of heart rate variability (HRV) and assessment of balance (BESS test). The Buffalo concussion treadmill test (BCTT), which is the most used physical activity test after SRC was performed on days 3 after SRC in control group and on 1st day after SRC in main group. The results of the study showed a association beetwen SRC and changes in autonomic regulation increasing sympathicotonia. In addition, we discover the dynamics of ANS stability during the early period of recovery after SRC. Also, we establish improvement of motor functions after SRC in the dynamics from 1st visit to 4th. However, despite the existing recommendations for early active rehabilitation on the third day after concussion, not taking into account the level of autonomic regulation can lead to physical overstrain of regulatory systems. This think shows the importance of taking into account the level of autonomic regulation while planning the rehabilitation and sports activities after SRC with ice-hockey players.